PROBLEMATIKA PERNIKAHAN DINI (Studi pada Masyarakat Kecamatan Balanipa Kabupaten Polewali Mandar) - Muh. Sudirman; Mustaring Mustaring; Nurul Fitriani (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2022)
This study aims to determine the factors that cause early marriage, problems that arise in the household for couples who do early marriage and the efforts made to minimize early marriage in Balanipa District, Polewali Mandar Regency. This type of research is qualitative research and uses a descriptive approach. The data sources used are primary data and secondary data. Data collection techniques include: Observation, Interview and Documentation. The data obtained from the research results were processed using descriptive qualitative data analysis. The results of this study indicate that; 1) There are several factors behind the occurrence of early marriage, namely parental factors, low awareness of the importance of education, self-will, and promiscuity factors. 2) As for the problems that arise in the household for couples who do early marriages, among others, quarrels and conflicts, economic problems, lack of a sense of responsibility and divorce. 3). As for the efforts made to minimize early marriage, namely, Raising awareness in the community about the importance of education for children and the younger generation, planting religious education for every child, and cooperation from the KUA Balanipa District.